Kinetics of transesterification reaction using CAO/AL2O3 catalyst synthesized by sol‐gel method. (12th March 2015) - Moradi, Gholamreza; Davoodbeygi, Yegane; Mohadesi, Majid; Hosseini, Shokoufe
<x xml:space="preserve">Abstract</x> Calcium oxide is one of the appropriate catalysts for biodiesel production. In this study, 40 wt. % CaO/Al2O3 catalyst was used. Transesterification reaction was performed in optimal condition presented in the previous study (0.05 molar nitric acid and gelation temperature of 70 °C) in a 250 mL two‐necked flask. All the experiments were carried out in the presence of soybean oil, methanol (methanol to oil molar ratio of 12:1), and catalyst concentration of 6 wt. %. Stirrer speed was set at 350 rpm. This study investigated the effects of reaction temperature and reaction time on produced biodiesel conversion. Methyl ester conversion changes in all temperatures and across different times indicated pseudo‐first order kinetic, so, first, the observed rate constant was obtained at various temperatures. Then, observed activation energy of soybean oil methanolysis in the presence of CaO/Al2O3 catalyst was determined. The results show that maximum errors of model are in primary times because methanol is insoluble in soybean oil. At the other times and by biodiesel and glycerol production, there was increased solubility of methanol in oil. The methyl esters production rate is related to diffusion of methanol in oil film and reaction rate constants which are calculated these constants.